High doses of inorganic zinc modulate the hypopharyngeal glands of Apis mellifera but promote abandonment of colonies when offered over long periods - Carillo, Marcela Pedraza [UNESP]; Astolfi, Aline [UNESP]; Rodrigues, Edgar Junio Damasceno [UNESP]; Lippi, Isabella Cristina de Castro [UNESP]; da SILVA, Letícia Garbin Ribeiro [UNESP]; Guimarães, Matheus Gardim [UNESP]; Justulin, Luiz Antônio [UNESP]; Orsi, Ricardo de Oliveira [UNESP] (My University, 2022)
Previous studies by our research group verified the beneficial effects of zinc supplementation on honey bee colonies during offseason. Here, we used high concentrations of inorganic zinc to evaluate the effects of high levels of zinc supplementation on hypopharyngeal gland (HPG) development of Apis mellifera L. during off-season. Twelve colonies were randomly assigned to one of four experimental diets (0 ppm Zn, 500 ppm Zn, 1000 ppm Zn, and 1500 ppm Zn) with three replicates. Honey bees received 500 mL of diet supplement with or without an inorganic source of zinc (sulfate heptahydrate, 20% zinc) once a week for 60 days. After the experimental period, 20 worker bees (6-days-old nurse bees) were sampled from each colony for HPG development analysis. Zinc, regardless of the level, increased the average area of acini compared to the non-supplemented group. However, gradual colony population reduction was visually observed after approximately 90 days, suggesting that Zn supplementation at high concentrations may exert a toxic effect. Therefore, although zinc can positively modulate HPG, the zinc supplements must be administered with caution.
Keywords: beekeeping; mineral supplementation; nutrition; protein